THE INFLUENCE OF ECONOMIC MENTALITY ON SOCIO-ECONOMIC DEVELOPMENT - Z. Halushka; V. Zapukhlyak; L. Klevchik; O. Luste; B. Storoshchuk (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. The current stage of socio-economic development is characterized by structural reforms connected with forming of competitive market environment, development of various forms of ownership, formation of qualitatively new forms of economic activity organization, deepening integration processes. Authors underline inconsistenciesbetween the interaction of the formal and historically formed informal institutions actualizes the role of economic mentality, since it directly influences the general vector of socio-economic system development. The article draws attention to the informal component of the institutional environment — economic mentality, which haracterizes the historically formed values, motives and models of economic behavior of individual and collective actors that directly affect the overall vector of socio-economic system development and transformation.It is determined that economic mentality determines the dynamics of the institutional environment development of by influencing the effectiveness of formal and informal institutions interaction, ensuring the performance of complementary functions; mediates the process of institutionalization of historically determined values, stereotypes and models of economic behavior in the system of formal norms and rules; provides under the influence of other socio-economic factors adaptability and dynamism of nstitutional structure, promotes the formation and development of new institutions. The aim of this research is to explore the relationship between economic mentality as a a long-term determinant of economic behavior and international indicators of economic system development. The methodology is based on the correlation-regression analysis to reveal the dependence between the indicators of the national economies efficiency and the dimensions of economic mentality by G. Hofstede. As a result the significant links can be traced between Gross National Income, Index of Economic Freedom, the Global Innovation Index and economic mentality indicators of Individualism, Power distance and Uncertainty avoidance index.